Managing work-in-process inventory - Kivenko, Kenneth (Industrial engineering, 1981)
Managing Work-in-Process Inventory is a practical manufacturing reference book that provides the necessary theories, models, mathematics, and practices for managing, planning, and controlling work-in-process (WIP) inventory.